On some approximate properties of biharmonic Poisson integrals in the integral metric - Zhyhallo, K.M.; Kharkevych, Yu.I. (Carpathian Mathematical Publications, 2024)
This paper is devoted to solving one of the extremal problems in the theory of approximation of functional classes by linear methods of summation of the Fourier series in the integral metric, namely, approximation of classes L^ψ_β, 1 by biharmonic Poisson integrals. As a result of the research, we have found the asymptotic equalities for the approximation values of classes of (ψ, β)-differentiable functions by biharmonic Poisson integrals, that is, have found solutions of the Kolmogorov-Nikol'skii problem for biharmonic Poisson integrals on classes L^ψ_β, 1 in the integral metric.